P35 A Physiologist-Led Interstitial Lung Disease Follow Up Service: Experiences and Outcomes in a UK District General Hospital. (19th November 2012) - Jones, MG; Butterfield, K; McConnell, W
Abstract : Introduction and Objectives: A proportion of patients with interstitial lung disease (ILD) maintain disease stability but require ongoing physiological and symptomatic monitoring. With increasing service demands and targets to reduce the proportion of follow up appointments, new approaches to use physician time efficiently whilst ensuring patient safety are required. In 2006, under the supervision of a Consultant Respiratory Physician, a Physiologist Led ILD service was established in our hospital. Based on the clinical decision of the physician, patients with stable ILD at follow up are transferred for physiologist led follow up for ongoing observation. All patients attend for pulmonary function tests under the supervision of a physiologist at an interval determined by the physician. At this visit a patient symptom questionnaire is completed, and, if requested by the physician, a chest radiograph is performed. The information is subsequently reviewed by the physician who determines whether ongoing physiologist led follow up, further physician input, or discharge from follow up is required. The Aim: of this study was to retrospectively review service demand and patient outcomes over a 6 year period. Methods: Retrospective database and case review of all patients transferred by one respiratory consultant for physiologist led follow up from January 2006 until December 2011. Results: 106 patients were transferred for physiologist led follow up. Mean age at commencement of follow up was 71.2. 29 patients were stable throughout follow up and discharged (mean number of visits per discharged patient 2.46). 8 patients required physician input based on change in symptoms or physiological parameters. 6 of these patients were diagnosed with progression of ILD and 3 commenced on treatment. 2 subsequently died from ILD. No patient died from ILD whilst under physiologist led follow up. In 2011 48 follow up appointments were saved from one consultant's clinic lists. Conclusions: With appropriate patient selection, physiologist-led ILD follow up provides a safe and effective service whilst reducing the demand placed on physician follow up appointments.